Tourism and resilience - Butler, Richard (CABI Books, 2017)
The focus of this book is on the application and relevance of the concept of resilience to tourism. As well as summarizing the growth of the concept in the social sciences and tourism especially, this book illustrates: (i) the key elements involved in making the concept relevant to communities; (ii) the ways in which it can be used to enable communities to mitigate the effects of disasters and conflict; (iii) the relevance to small and highly vulnerable communities; (iv) how it can be significant to the tourism industry even in the most commodified of settings; and (v) its role in a changing political world. Part 1 (chapters 1-3) discusses the original definitions and applications of the concept in the natural sciences and its being adopted and adapted in the social sciences. Part 2 (chapters 4-6) examines resilience in a socio-ecological setting, whereby the concept is used to bring together the relevant ecological issues and the social science counterparts in terms of the way the concept could be applied in tourism destination communities. Part 3 (chapters 7-9) explores ways to deal with post-conflict and post-disaster situations in tourism using resilience measures. Part 4 (chapters 10-13) examines resilience in those settings in which it is already a familiar context: remote and insular communities and protected areas. Part 5 (chapters 14-16) focuses on the tourism industry, its economic and political links and relationships by exploring resilience and sustainability along with responsibility.